The Role of BUMDES in Increasing Village Original Income and the Village Community Economy in Sigi Regency - Umar; Rasmi Nur Anggraeni (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
This study aims to analyze the role of Bumdes in increasing village original income and the economy of rural communities in Sigi Regency. The research method uses a Community Based Research approach which is carried out in a qualitative descriptive manner. The research population is all Village-Owned Enterprises in Sigi Regency, while the research sample is determined by purposive sampling technique. Data collection techniques were carried out through observation, interviews, Focus Group Discussion (FGD), and data analysis techniques using qualitative analysis. The results showed that BUMDes could increase Village Original Income but not significantly, and BUMDes had not been able to improve the economy of rural communities. This is due to the limited capacity of human resources, small capital participation, and the type of business managed by BUMDes is still small in scale so that it has not opened up job opportunities for rural communities. Furthermore, the results of the research become the basis for the preparation of a follow-up plan in the form of developing human resource capacity, strengthening governance and management, financial management, and developing BUMDes business.